FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) DI JAWA TENGAH - Yulinda Setiawan, 08.05.52.0019; Kartika, Andi (Students Journal of Accounting and Banking, 2012)
Taxesare one source ofstate revenueisvery important for the implementation andenhancementof national development. Tax revenuesthat provideconsiderable contribution to thereceptionareaisland and building tax. This was provenduring theyears2008-2010land and building taxin the formerresidency of Semarangon the increase. The purposeof this studyis to measurehow much influence GDP percapita, population andland area of land and building tax receipts(PBB) districts in the province of Central Java. This studyuses multiple linear regression analysis method because it uses more than one independent variable. The results of this study indicateallindependentvariableshave a positiveand significant impact onland and building taxreceipts.Keywords: PBB, GDP percapita, population and number ofland area.